Initial Dynamics of Financial Markets in the Transition Economies in the 1990s and New Critique of the Big Bang Policy: Heterodox Approach - Rozmainsky, I.V. (Економічний вісник Донбасу, 2010)
Heterodox — Post Keynesian and Institutionalist — economics proves that expansion of financial sector can be harmful for the real sector. Such conclusion is an effect of account of variability of preferences, planning horizons and degree of rationality in the behavior of economic agents. We suppose that both methodology and conclusions of Heterodox Economics can be especially topical for many transition economies. The point is that fundamental features of the transitional economies affect the patterns of choice of agents in the financial markets. These patterns, in turn, lead to the adverse effects of the expansion of financial markets in such economies. Key words: Financial Markets; Transitional Economies; Economics of Transition; Rationality; Heterodox Economics. Неортодоксальна — посткейнсіанська та інституціональна, — економіка доводить, що розширення фінансового сектора може бути шкідливим для реального сектора. Такий висновок: ефект урахування мінливості переваг, горизонтів планування та ступеня раціональності в поведінці економічних агентів. Ми припускаємо, що і методологія, і висновки неортодоксальної економіки можуть бути особливо актуальні для багатьох перехідних економік. Річ у тім, що фундаментальні особливості перехідних економік впливають на схеми вибору агентів на фінансових ринках. Ці зразки, у свою чергу, приводять до несприятливих ефектів розширення фінансових ринків в таких економіках. Ключові слова: Фінансові Ринки; Перехідні Економіки; Економіка Переходу; Раціональність; Неортодоксальна Економіка. Неортодоксальная — посткейнсианская и институциональная, — экономика доказывает, что расширение финансового сектора может быть вредно для реального сектора. Такое заключение — эффект учета изменчивости предпочтений, горизонтов планирования и степени рациональности в поведении экономических агентов. Мы предполагаем, что как методология, так и выводы неортодоксальной экономики могут быть особенно актуальны для многих переходных экономик. Дело в том, что фундаментальные особенности переходных экономик воздействуют на схемы выбора агентов на финансовых рынках. Эти образцы, в свою очередь, приводят к неблагоприятным эффектам расширения финансовых рынков в таких экономиках. Ключевые слова: Финансовые Рынки; Переходные Экономики; Экономика Перехода; Рациональность; Неортодоксальная Экономика.